Trade dynamics and trade costs: First evidence from the exporter and importer dynamics database for Germany - Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2015)
This note uses the newly available Exporter and Importer Dynamics Database for Germany to investigate the links between trade dynamics and trade costs. It shows results for the dynamics of Germany's goods trade as a whole, and for trade with two of the most important partner countries, namely France and China. Furthermore, it reports results from the first empirical study that searches for links between measures of trade dynamics (entry, exit and survival rates, and share of entrants, in total exports and imports) in destination countries of exports and countries of origin of imports on the one hand and characteristics of these countries (distance to Germany, difficulty of foreign trade, and market size) on the other hand.
Keywords: F14; 330; exports; imports; transaction level data; Germany